Atherogenic index of plasma and risk of cardiovascular disease among Cameroonian postmenopausal women. Issue 1 (December 2016) - Nansseu, Jobert; Ama Moor, Vicky; Nouaga, Murielle; Zing-Awona, Bertrand; Tchanana, Gladys; Ketcha, Arthur
Abstract Background The paucity of data regarding the relationship between atherogenic index of plasma (AIP) and risk of cardiovascular disease (CVD) in postmenopausal women living in sub-Saharan Africa prompted us to conduct this study which aimed at assessing the interplay between AIP and risk of CVD among Cameroonian postmenopausal women. Methods This was a cross-sectional study conducted among 108 postmenopausal women in Yaoundé, Cameroon. Risk of CVD was calculated using the Framingham risk score, (FRS), and the AIP was derived as log (triglycerides/high-density lipoproteins cholesterol). Results Mean age of participants equaled 56.4 ± 6.9 years. AIP values ranged from -0.40 to 0.85 with a mean of 0.21 ± 0.27. There was a positive and significant correlation between AIP and body mass index (r  = 0.234;p  = 0.015), systolic blood pressure (r  = 0.350;p  < 0.001), diastolic blood pressure (r  = 0.365;p  < 0.001), fasting plasma glucose (r  = 0.314;p  = 0.001), uric acid (r  = 0.374;p  < 0.001), and total cholesterol (r  = 0.374;p  < 0.001), but not with age (r  = -0.104;p  = 0.284). The FRS varied between 1.2 % and >30 % with a mean of 13.4 ± 8.7 %. In univariable model, AIP significantly influenced the risk of CVD (β = 11.94;p  < 0.001; R2  = 0.136). But in the multivariable model, after adjusting for confounders, AIP did not impact the risk of CVD anymore (adjusted β = 1.98;p  = 0.487; R2  = 0.486). Conclusion AIP may not be an independent factor impacting the risk of CVD among Cameroonian postmenopausal women. More studies are needed to better elucidate the interaction between AIP and risk of CVD in our setting.